PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT PADA PERUSAHAAN NON KEUANGAN PERIODE 2011-2013 - PUTRI W., SENDY (Jurnal Akuntansi AKUNESA, 2015)
The purpose of this study to analyze the influence of Corporate Governance (independent commissioner, board of commissioner size, institusional ownership, auditor reputation) and Firm Charactheristic (firm size, leverage,bussiness complexity) to Enterprise Risk Mangement Disclosure. This research was based on non-financial companies listed of Indonesian Stock Exchange in 2011-2013. Samples were collected by purposive sampling method and was analyzed with multiple regression analysis.The results showed that board of commissioner size, institusional ownership, auditor reputation, firm size and bussiness complexity have significant on enterprise risk management disclosure, but other variable which are independent commissioner and leverage does not have a significant effect on enterprise risk management disclosure. Keyword: Enterprise risk management, corporate governance, firm characteristic